The Effect of Using Kahoot! on Students’ Level of Understanding in Fiqh Classes - Dewi Khairunisa; Abdul Azis Khoiri; Darnanengsih (IQRO: Journal of Islamic Education, 2026)
The issue explored in this study stems from how Fiqh is often taught in a rather conventional way. In many cases, students simply listen, take notes, and move on, without really being involved in the learning process. Over time, this kind of approach seems to contribute to a lower level of understanding. With that in mind, the study sets out to examine whether using Kahoot! as a learning media can actually make a meaningful difference. A quantitative approach was used, applying a one group pretest-posttest design. The participants were 20 ninth-grade students from MTs Al-Ma’arif 2 Sorong Regency, selected through purposive sampling. Data collection relied on pretest and posttest instruments, supported by observation and documentation. For the analysis, the Shapiro-Wilk normality test was conducted first, followed by the Wilcoxon Signed Ranks Test. The findings show a noticeable increase in the mean score, from 60.50 to 78.50. The significance value of 0.033, which is below 0.05, indicates that the use of Kahoot! has a statistically significant effect on students’ understanding. In a way, this suggests that the platform does more than just make learning feel lively; it also helps students grasp Fiqh material in a more effective and meaningful way.